PENYEBARAN BATUAN GRANIT DAN SEDIMEN KUARTER BERDASARKAN INTERPRETASI DATA SEISMIK DI PERAIRAN BATAM UTARA - Ediar Usman (Pusat Survei Geologi, 2007)
Results of mappings and publications concerning the distribution of granite and Quaternary sediments in territorial waters of Batam Island and its surroundings are still limited. It is caused by the distribution of the granite which emerges to sea bottom in territorial waters in the part of the North Batam and its surroundings is also limited. Results of seismic interpretation show the existence of some reflector characteristics of the granite and the Quaternary sediments. Based on the interpretation model at bedrock and the Quaternary sediment, distribution area of the bedrock is in part of west and north of Batam Island and also in the part of the north of Bintan Island. While the Quaternary sediment, based on reflector seismic characters, is coarse fluvial deposits at the bottom as the channel fill between some domes of granite body and recent marine deposits at the top. If the bedrock is correlated with regional geology in territorial water of the Batam Island and its surroundings,the bedrock is granite. Keywords: granite, bedrock, Quatenary sedimen,seismic interpretation ,North Batam